BIBLICAL WAY OF PRAYER - Nereparampil, Lucius (Journal of Dharma, 1985)
Centuries ago Paul, a great man of God, wrote thus about prayer: ..... we do not know how to pray as we ought, but the Spirit himself intercedes for us with sighs too deep for words" (Rom 8:26). Yes, a man left to himself is incapable of praying properly. But if he is assisted by God's Spirit, he can look up to God and call him "Abba!", "Father!", and thus engage himself in authentic prayer.' The Bible being a sacred book inspired by the Spirit of God, offers many ways of prayer and thus teaches us how to pray. In this context, a study of these biblical ways of prayer is of great importance, and hence the scope of this article. Since the limited space of this article does not permit us to examine elaborately all the instances of prayer found in the Bible, which would indeed be too vast, in this short essay we confine ourselves to certain areas of the Bible, the analysis of which would give invaluable know- ledge about the biblical way of prayer.